Spectrum Sensing under Correlated Antenna Array Using Generalized Detector in Cognitive Radio Systems - Modar Safir Shbat; Vyacheslav Tuzlukov (International Journal of Antennas and Propagation)
We derive the probability of false alarm and detection threshold under employment of the generalized detector (GD) in cognitive radio (CR) systems for two scenarios: firstly, the independent antenna array elements; the secondly, the correlated antenna array elements. The energy detector (ED) and GD spectrum sensing performances are compared under the same initial conditions. The simulation results show that implementation of the GD improves the spectrum sensing performance in CR systems both for independent and correlated antenna array elements.